In-Vivo Alpha-Amylase and Alpha-Glucosidase Inhibitory Activities of Solanum anomalum Leaf Extract and Fractions - Jude Efiom Okokon; Idongesit Charles Etuk; John Akpan Udobang; Nwakaego Omonigho Ebong (Biology, Medicine, & Natural Product Chemistry, 2023)
Solanum anomalum Thonn. ex Schumach. (family Solanaceae), an edible shrub whose fruits and leaves are used medicinally to treat diseases including diabetes was evaluated for effect on alpha amylase and alpha glucosidase enzymes in vivo. The leaf extract (70-210 mg/kg) and fractions (hexane, dichloromethane, ethyl acetate, methanol, 140 mg/kg) of S. anomalum were evaluated in vivo for inhibitory effect on alpha amylase and alpha glucosidase enzymes using starch, sucrose and maltose as substrates. Acarbose was used as reference drug. The leaf extract especially middle dose (140 mg/kg) and fractions (ethyl acetate and hexane) caused significant (p<0.05) reduction in blood glucose levels of treated with the various substrates used. Ethyl acetate fraction exerted the highest inhibitory effect when starch and maltose were used as substrates followed by n-hexane and methanol. n-Hexane was the most active fraction followed by ethyl acetate when sucrose was used as substrate. The results suggest that the leaf extract and fractions of S. anomalum have the potentials to inhibit alpha amylase and glucosidase in rats.